Sustainability of Mount Zawa in Duhok: A study in physical geography using the SWOT tool - Mohammed, Laylaf Dishwar (Journal of Tikrit University for Humanities, 2024)
Sustainable development of natural resources of the area through studying the natural characteristics. It is located in the northern part of Iraq and is confined between brackets length(“0،’55،°42 (“0، ؘ10،°43) (east and respectively two latitudes length (36°, (“5،’51 (“55،ؘ47،°38)north and respectively,with an area of approximately(47.15)KM2. Geographical the largest part of it lies within the Injana formation in (49,99)% and the opening formation which reached a percentage of (28.81)%.It is characterized by porosity and permeability, the erosion rate decreases which bring out some geomorphological features of the region which have added attractive forms to tourism,such as caves. The soil of the region was divided according to the BURINGH classification into two parts. The first is rugged,cracked, rocky land affected by water erosion, and it is the largest in area. The second is brown soil with deep thickness represented by the soil of the valleys of the undulating mountainous region with the highest elevation estimated at approximately (1,000 m), and the lowest elevation of the area (460 m) above sea level. SWOT tool was applied to shed light on the strengths and address weaknesses as it is based on the natural aspects to develop the future development of the region.